Monitoring of an old metallic bridge by using of electric and optic technologies - Bruno J. A. Costa (2009)
This article presents and discusses the monitoring systems installed in the Trezói Bridge, within the research project named Assessment of the Structural Integrity of Metallic Railway Bridges whose scope was to develop and apply procedures for evaluation of the structural integrity of metallic railway bridges. The field observations of the structural behavior were accomplished by using two different types of sensors: electric and fiber optic. The results obtained by both are analyzed and the capabilities and limitations to acquire the relevant data for fatigue assessment are discussed.